The Latent Function of the Production Council - Ben-Porat, A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
The author presents a functional analysis of the Production Council in Israeli industry. He first presents the P.C.’s manifest function and discusses its existence and reasoning. He then provides a latent function interpretation of the phenomenon and suggests that this interpretation adequately explains the phenomenon and contributes to its understanding within the enterprise context.